2016
DOI: 10.1111/1462-2920.13544
|View full text |Cite
|
Sign up to set email alerts
|

CAZyme content of Pochonia chlamydosporia reflects that chitin and chitosan modification are involved in nematode parasitism

Abstract: Summary Pochonia chlamydosporia is a soil fungus with a multitrophic lifestyle combining endophytic and saprophytic behaviors, in addition to a nematophagous activity directed against eggs of root‐knot and other plant parasitic nematodes. The carbohydrate‐active enzymes encoded by the genome of P. chlamydosporia suggest that the endophytic and saprophytic lifestyles make use of a plant cell wall polysaccharide degradation machinery that can target cellulose, xylan and, to a lesser extent, pectin. This enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 87 publications
0
50
0
Order By: Relevance
“…Our results show that mycelium of P. chlamydosporia derived from chlamydospores can grow with chitosan as the only carbon source. The large expansion of GH75 chitosanase family in the genome of P. chlamydosporia ( Aranda-Martinez et al, 2016 ) could explain this feature.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that mycelium of P. chlamydosporia derived from chlamydospores can grow with chitosan as the only carbon source. The large expansion of GH75 chitosanase family in the genome of P. chlamydosporia ( Aranda-Martinez et al, 2016 ) could explain this feature.…”
Section: Discussionmentioning
confidence: 99%
“…Their differences are mainly in the S08A (31 vs. 25), S09X (63 vs. 68), S10 (14 vs. 16), M43B (18 vs. 14), C14B (3 vs. 6), and I09 (5 vs. 2) families. The subtilisin (S08A) and carboxypeptidase (S10) enzymes may be involved in host recognition and pathogenicity, like the well-known VCP1 and SCP1, which are related to nematode egg penetration 14 , 15 , 17 . An overexpression of VCP1 and SCP1 under stress increases fungal capabilities to parasitize nematode eggs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Two secreted serine proteases (VCP1 and SCP1) and one secreted chitinase (PCCHI44) from P. chlamydosporia have been reported to be involved in nematode egg infection 14 16 . A recent study describes activity of chitin deacetylases (CDA1 and CDA2) together with chitosanases (CSN1-CSN9) as a determinant protein during nematode egg infection by P. chlamydoporia 17 . Transcriptome analysis shows that a large fraction of secreted proteins in the P. chlamydosporia strain 123 (PC123) genome are expressed during the endophytic process 12 , suggesting essential roles for secreted proteins in the multiple lifestyles of P. chlamydosporia .…”
Section: Introductionmentioning
confidence: 99%
“…One of the features of egg-parasitic fungi is their ability to penetrate the chitin layer in the eggs. Further proof of this has been obtained in recent studies when chitosan was found during nematode egg infection, an advantage for the adaptation of biocontrol fungi to their natural environment (Aranda-Martinez et al 2016). This feature of chitosan production has been taken further by Aranda-Martineza et al (2017), showing that ethylene can be produced from chitosan using nematophagous and entomopathogenic fungi.…”
Section: Introductionmentioning
confidence: 87%